Leonard Borkowicz’s Ideological Choices and His Autobiographical Account of Communism - Rembacka, Katarzyna (Sensus Historiae, 2021)
From the age of fifteen Leonard Borkowicz was associated with the communist movement in Poland. He had the potentials to become a role model communist - he was a strong believer, he was devoted and he was loyal. However, as time passed, he became increasingly critical of both his ideology and his role in the system. The autobiographical materials left behind by Borkowicz, which primarily include the typescript of a never published book and his unpublished personal notes from the time of martial law, allow us to follow his ideological evolution. They also make it possible to face the questions: why did he become involved with the radical left movement? What changes did he undergo from ideological point of view? What did lead him to become a strict anti-communist? Did he feel responsible for the system he co-created and, if so, what was his way of expressing it?